"New chronic" patients. Issue 6300 (31st October 1981) - Bewley, T H; Bland, M; Mechen, D; Walch, E
Abstract : A five-year follow-up of 1467 mental hospital patients showed that 501 had died, 449 had been discharged, and 517 were still resident. During this period 81 "new chronic" patients aged under 65 were admitted: 49 were readmissions and 15 of 32 first admissions had had previous periods in other psychiatric hospitals. Many new chronic patients were old chronic with intervals of community care, and one-third of them were likely to require permanent care. These findings provide no comfort for those who believe that present DHSS plans for mental health services can ever be realised.